A STUDY ON ERRORS IN USING PUNCTUATION MADE BY STUDENTS OF SMAN 2 TAPUNG IN WRITING NARRATIVE TEXT - Hanny Sarah Yolanda Sijabat; Dahnilsyah Dahnilsyah; Syarfi Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study discusses student’s errors in using punctuation when writing narrative text and analyzes what possible causes of errors in writing punctuation in narrative text which made by the tenth year students of SMAN 2 Tapung. In this study, 30 students employed were taken as the sample of this research. These 30 students consits of 3 classes, there for classes X1, X2, and X3, each class is taken 10 students. This study used descriptive qualitative research. The descriptive qualitative data were collected from the tests by filling the correct punctuation marks in the narrative text that has been provided. The findings of this study indicate that students still do not understand the use of punctuation in writing narrative text. The punctuation marks used in this study are comma, period, capital letter, exclamation marks and question marks. There are many errors in the use of capital letter. However, in the use of question marks, students’ abilities can be categorized as good. This phenomena happened because the students are lack of knowledge about punctuation, and the students still confused to apply the type of punctuation. Key Words: Errors, Punctuation, Narrative Text